Spontaneous Clearance of Hepatitis C Virus during Pregnancy. (March 2013) - Clohessy, Penelope; Polis, Suzanne; Post, Jeffrey
Spontaneous clearance of hepatitis C virus (HCV) is expected to be unlikely in pregnancy due to the relative immunosuppression and increase in viraemia that occurs. We report the first case of spontaneous clearance of hepatitis C virus (HCV) occurring in pregnancy.